Pengaruh Status Sosial dan Kondisi Ekonomi Keluarga terhadap Motivasi Bekerja bagi Remaja Awal (Usia 12-16 Tahun) di Kabupaten Ponorogo - Wijianto Wijianto; Ika Farida Ulfa (Universitas Darussalam Gontor, 2016)
In Ponorogo which is one of the districts in East Java, still have a high dropout rate. The dropout rate or children who do not continue their education to a higher level is mainly due to socio-economic status of the child. Children who do not attend school to higher levels experienced by many children completing elementary school, where the child has stepped on early teens (aged 12-16 years) who do not attend school. The preferring to work to help the economy of parents who are still below the poverty line. Children who stepped on early teens is more work in the agricultural sector and the building became a construction worker. Not a few of the young women who choose to take urbanization into town and become housemaid. The result showed that there was no significant effect of social status on work motivation early teens in Ponorogo. The influence of social status variables on work motivation is small, making it less contributed to the high-low work ethic early teens in Ponorogo. This means that the socio-economic conditions of the early teens in Ponorogo not significantly affect the work motivation early teens in Ponorogo. The second discovery was no significant effect of economic conditions on work motivation early teens in Ponorogo. This means that their economic condition is not good to have an impact on work motivation early teens in Ponorogo.